Dysfunctional Constitutionalism or Dysfunctional Politics: A~Matter of Law, Politics, and Institutional Design - Roland Lhotta (Politische Vierteljahresschrift, 2023)
The following reflections are an attempt in constitutional theory to adress the core elements of the U.S. constitutional crisis. It will first identify structural and normative properties of the U.S. Constitution that may become battlegrounds for adversarial ideas, meanings, logics of appropriateness, and, finally, institutional and constitutional missions, all centering around constitutional liberty. In a~second step, it will be shown that institutional theory addresses important links between norms/rules/institutions and actors/citizens that are crucial for a~constitution and its potential normative battlegrounds. It is alleged that a~constitutional crisis is closely related to incommensurable interpretations of constitutional value choices (e.g., liberty) and the ways actors choose to make their interpretations actionable through the institutional channels of a~polity. Constitutional theory, hence, should consider institutionalist findings in order to come to grips with the phenomenon of constitutional crisis. Third, in this light it will be discussed whether the prevailing models of (U.S.) constitutionalism are able to assimilate defects in the crucial relationship between the constitution and actors, especially when it comes to factionalized and polarized meanings and interpretations—which in turn trigger adversarial institutional/constitutional missions and may lead to constitutional wars. Fourth and finally, these reflections are taken together for an outlook on the prospects of constitutional development in the United States and the challenges that lie ahead.
Keywords: 320; Rights; Interpretation; Federalism; Checks and balances; Polarization; Rechte; Föderalismus; Gewaltenteilung; Polarisierung